Optimizing control structure and branching learning with flipbook-based e-module for software engineering students - Febrianti, Ria; Tuwoso, Tuwoso; Hidayat, Wahyu Nur; Wardani, Yurike (Jurnal Pendidikan Teknologi Kejuruan, 2025)
This research highlights the significance of developing innovative learning media to enhance effective learning for class X Software Engineering (RPL) students at SMK Negeri 4 Malang. The study addresses the need to improve student engagement and deepen understanding of concepts, particularly in Control Structure and Branching material. The primary objective is to create an interactive and innovative Flipbook-based e-module as practicum media to support the learning process. Using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), this research employs a systematic and structured approach in developing learning products. The Flipbook-based e-module achieved a feasibility score of 90% from material experts and 97.5% from media experts, indicating its high validity and feasibility. During the trial phase, the e-module obtained feasibility score of 89% from a small group and 90% from a large group, resulting in an average feasibility score of 89.5%. These findings demonstrate that the Flipbook-based e-module is highly suitable for implementation in the Vocational Basics subject for class X RPL students at SMK Negeri 4 Malang. Additionally, the small group test showed a student learning motivation score of 85.4%, while the large group test yielded 87%, with an average of 86.2%. This indicates that the developed product significantly supports students’ learning motivation, proving its high validity in improving engagement and understanding. These results affirm the Flipbook-based e-module is potential as an effective learning tool for vocational education.